New substitute name for the genus Dayus Steiner & Amaral, 1999 (Annelida: Polychaeta: Histriobdellidae) - Zhang, Yu-Tao (Zootaxa, 2014)
The annelid genus Dayus was established by Steiner and Amaral (1999) for a single species Stratiodrilus cirolanae Führ, 1971 from South Africa. Nevertheless the genus name Dayus is preoccupied and was initially introduced by Mahmood (1967) for a typhlocybine leafhopper genus with Dayus elongatus Mahmood, 1967 as the type species from Singapore (Insecta: Hemiptera: Cicadellidae). Thus, the genus Dayus Steiner & Amaral, 1999 is a junior homonym of the genus Dayus Mahmood, 1967. According to Article 60 of the International Code of Zoological Nomenclature (ICZN 1999), I propose the new replacement name Steineridrilus nom. nov. for Dayus Steiner & Amaral, 1999. The resulting nomenclatural changes are summarized below.